Tinjauan Filosofis Guru Pendidikan Agama Islam Humanis-Multikulturalis - Rohman, Miftahur (Institut Agama Islam Negeri (IAIN) Tulungagung, 2018)
As a millennial generation, learners tend not to have maturity in thinking. The seeds of exclusive, intolerant, even radical thought become an alarming threat. Moreover, teachers as educators play a substantial role in introducing the values ââof humanism and multiculturalism. With the study of library research and analysis with content analysis method, this research tries to formulate the concept of Islamic religious education teacher of multiculturalism to the generation of humanist-democratic Islam. The results concluded that multicultural education becomes an alternative solution to overcome the disintegration of the nation that began to occur. Teachers as learning facilitators should design learning that supports the implementation of multicultural education. Terefore, it needs a multicultural typology teacher who can appreciate the deversity, upholds human rights and justice, avoiding theological justification and truth claims, and non-constructive anti-criticism. It can be concluded that it has implications on the achievement of true Islamic education objectives, namely to educate students academically, spiritually, and socially.